CHINA’S ECONOMIC UNCERTAINTY AND FOREIGN DIRECT INVESTMENT IN INDONESIA: Bahasa Inggris - Ulfa, Maria Aulia; Febriani, Ratu Eva (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
The study examines the effects of China’s economic policy uncertainty, trade openness, inflation, and the human development index on foreign direct investment (FDI) in Indonesia. This study uses multiple linear regression on annual data from 1995–2022. This research shows that China’s economic policy uncertainty has a negative but significant on Indonesia’s foreign direct investment while HDI, trade openness, and inflation all have a positive and significant impact on Indonesia’s foreign direct investment. The study’s findings indicate that trade openness, inflation, human development index, and China’s economic policy uncertainties all have an impact on foreign direct investment, So, the government needs to estimate and monitor direct investment funds coming in, especially from China. To advance the nation, especially the welfare of society, there must be an increase in quality human resources. To draw in investors, it’s also essential to raise transparency and manage the pace of inflation.